P300 somatosensory validation of vibrotactile haptic feedback for upper limb prosthesis - Nur Amalina, Has; Mohd Najeb, Jamaludin; Sujana, Mohd Rejab; Zulkifli, Ahmad@Manap; Nurul Farha, Zainuddin; Abdul Haris, Abdul Salam; Ai Reen, Chu; Muhammad Amir, As'ari (Institute of Electrical and Electronics Engineers Inc., 2021)
Haptic sensation research based on the event's related potential (ERP) has been carried out extensively in order to help amputees to be able feel and control their prosthetic hand. Clinically, somatosensory evoked potential is suggested in the pain-related evoked potential and able to control a computer using a brain to computer interface system called BCI. Somatosensory response can be evoked by tactile vibrators whether it is directly and indirect contact with skin. Somatosensory evoked potential has been reported to have lower signal to noise ratio compared to the common visual evoked potential. P300 based on somatosensory evoked potential were discovered as a benchmark that a person will generate P300 whenever decision making as simple as lift their finger take place. The aim of this paper is to identify the best location of the upper limb for tactile haptic placement and investigating whether the vibration motor haptic tactile setup reflect on the P300 somatosensory response from encephalography recordings. Results show that most of the subjects correctly guesses during upper arm position of haptic tactile feedback than the lower arm position. The vibration motor haptic tactile feedback setup was validated via experiment with mental task in order to elicit P300 somatosensory event related potential (ERP).